Knowledge and reality in nine questions : a first book in philosophy - Davidson, Matthew, 1972- (London, England : Zed Books, 2021)
"For the Ancient Greek thinkers Plato and Aristotle, questions about philosophy concerned the fundamental nature of reality. This introduction is based on their views, boiling philosophy down to nine essential questions and using them to reveal how we think about the major topics of metaphysics and epistemology. It is a fast-paced tour of the Western philosophical tradition, walking you through age-old questions about God, free will, skepticism, truth and perception and introducing you to distinctive features and methods. By unpacking and exploring each of the nine questions in turn, you find out what it really means to do philosophy"--
Introduction -- 1. A Bit About Philosophy: What Are Thought Experiments? 2. What Am I? 3. Can Technology Make us Immortal? 4. Skepticism, or What If I Can't Tell if I'm in the Matrix? 5. What Is It to Act with Free Will? 6. Can We Know God? 7. What is Time? 8. What is Truth? 9. Are Objects of Perception All in our Mind? 10. Do Fictional Characters Really Exist? Bibliography Index -- Glossary Annotated Bibliography Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: First philosophy; Reality; Metaphysics; Knowledge, Theory of; Ancient philosophy; Philosophy: epistemology & theory of knowledge; Electronic books